Beyond Borders Stories of Yunnanese Chinese Migrants of Burma - Chang, Wen-Chin (Cornell University Press, 2014)
The Yunnanese from southwestern China have for millennia traded throughout upland Southeast Asia. Burma in particular has served as a "back door" to Yunnan, providing a sanctuary for political refugees and economic opportunities for trade explorers. Since the Chinese Communist takeover in 1949 and subsequent political upheavals in China, an unprecedented number of Yunnanese refugees have fled to Burma. Through a personal narrative approach, Beyond Borders is the first ethnography to focus on the migration history and transnational trading experiences of contemporary Yunnanese Chinese migrants (composed of both Yunnanese Han and Muslims) who reside in Burma and those who have moved from Burma and resettled in Thailand, Taiwan, and China.